Plasma Lipid Profile and Systemic Inflammation in Patients With Cancer Cachexia - Riccardi, Daniela Mendes dos Reis; das Neves, Rodrigo Xavier; de Matos-Neto, Emidio Marques; Camargo, Rodolfo Gonzalez; Lima, Joanna Darck Carola Correia; Radloff, Katrin; Alves, Michele Joana; Costa, Raquel Galvão Figuerêdo; Tokeshi, Flávio; Otoch, José Pinhata; Maximiano, Linda Ferreira; de Alcantara, Paulo Sérgio Martins; et al. (Frontiers in Nutrition, 2020)
Cancer cachexia is a syndrome inducing severe and fast involuntary weight loss. It affects around 80% of patients with advanced cancer and is by itself direct cause of death. Recent studies have shown that inflammatory mediators are active players in the development of cachexia. The white adipose tissue (WAT) is a contributor to inflammation as it suffers morphological reorganization and marked lipolysis, releasing free fatty acids (FFA), which accentuate the production of pro-inflammatory cytokines through the activation of pro-inflammatory signaling pathways. The aim of this study was to characterize the plasma lipid profile of cachectic patients and to correlate its FFA composition with that of inflammatory markers; finally, we sought to establish whether the fatty acids released by adipocytes trigger and/or contribute to local and systemic inflammation in cachexia. The study selected65 patients further divided into 3 groups: control (N); weight stable cancer (WSC); and cachectic cancer (CC). The plasma FFA profile was significantly different between the groups and was positively correlated with pro-inflammatory cytokines expression in CC patients. The changes in CC plasma characterize systemic inflammation and concomitant change in FFA profile.